The fate of phenomenology Heidegger's legacy - McNeill, William, 1961- (New Heidegger research., 2020)
In this important new book, leading Heidegger scholar William NcNeill provides a concise and systematic appraisal of the fate of phenomenology in Heidegger. He shows how the issue of "letting be" is already central and prominent in Heidegger's early phenomenology and examines Heidegger's phenomenological approach in relation to art and poetry.